Ответы и объяснения

Лучший Ответ!
  • Aluk
  • середнячок
2013-05-20T21:12:00+04:00

 Для начала найдем НОЗ: (3-x)(x+3)

 

                                         3x^2+9x+27-9x                                                                   

                                         ---------------------=x

                                                (x+3)(3-x)

                                        3x^2+27

                                        -------------=x                            Найдем КЗ: Х не равен -3 и Х не равен 3

 

                                        (x+3)(3-x)

  3x^2+27=x(x+3)(3-x)

  3x^2+27=x(9-x^2)

  3x^2+27=9x-x^3

  x^3+3x^2-9x+27=0 

 

  x^2(x+3)-9(x+3)=0

 

  (x+3)(x^2-9)=0

  x=-3(искл.)              x=3(искл.)

 

                                                                    Ответ: Корней нет